Distribution of high- and low-risk human papillomavirus genotypes and their prophylactic vaccination coverage among West African women: systematic review - Rogomenoma Alice Ouedraogo; Ali Kande; Wendyam Marie Christelle Nadembega; Djeneba Ouermi; Théodora Mahoukèdè Zohoncon; Florencia Wendkuuni Djigma; Charlemagne Marie Ragnag-Newende Ouedraogo; Olga Mélanie Lompo; Jacques Simpore (Journal of the Egyptian National Cancer Institute, 2023)
Abstract Introduction The second most deadly gynecological cancer worldwide, cervical cancer is steadily on the rise in sub-Saharan Africa, while vaccination programs are struggling to get off the ground. This systematic review’s aim was to assess the prevalence and distribution of high- and low-risk HPV genotypes in West African women. Methods Original studies were retrieved from PubMed/Medline, Embase, Scopus, Google Scholar, and Science Direct. In these studies, Human papillomavirus (HPV) DNA was assessed in cervical samples by polymerase chain reaction (PCR), Hybrid capture, and sequencing. The quality of the articles was assessed and the results were extracted and reviewed. Results Thirty-nine studies from 10 West African countries were included for the systematic review including 30 for the pooled analysis. From an overall of 17358 participants, 5126 of whom were infected with at least one HPV genotype, the systematic review showed a prevalence varying from 8.9% to 81.8% in the general population. In contrast, the pooled prevalence of infection was 28.6% (n = 3890; 95% CI 27.85–29.38), and HPV-52 (13.3%), HPV-56 (9.3%), and HPV-35 (8.2) were the most frequent. Quadrivalent and nonavalent vaccines covered 18.2% and 55.8% of identified genotypes respectively. Conclusion Faced with this growing public health challenge in West Africa, it would be necessary for all its countries to have reliable data on HPV infection and to introduce the nonavalent vaccine. A study of the genotypic distribution of HPV in high-grade precancerous lesions and cervical cancer would be very useful in West Africa.